EQ and leadership in Asia : using emotional intelligence to lead and inspire your people - Henry, Sebastien (Singapore : Jossey-Bass, an imprint of Wiley, 2011)
Numerous studies have provided conclusive evidence that Emotional Intelligence is crucial in leadership in the business environment. It is even more crucial in Asia where there is a higher tendency for emotions to be hidden beneath the surface of daily business interactions. Emotions are assets for a leader when wisely used, and a source of disruption if ignored. EQ and Leadership in Asia provides business leaders in Asia with the keys to using emotions as allies to face practical leadership challenges. In the first part of this book, Emotional Intelligence is presented in a clear way, in all.
pt. 1. Understanding emotional intelligence in Asia -- pt. 2. Using emotions as allies in practical leadership challenges.
Includes bibliographical references and index.
Print version record.
English.
John Wiley and Sons
Keywords: Emotional intelligence -- Asia; Leadership -- Asia; z; Leadership -- Asie; Emotional intelligence; Leadership; Asia; dissertations; Academic theses; Academic theses; 2